Espaço e discursos de identidade na Feira Hippie de Ipanema - Pinheiro, Luciano Tardin (1999)
The subject of this research is the identity of the Feira Hippie de Ipanema, a -handicrafts and popular art market for tourists. The identity discourses investigated were traced in the Market by analysis of its history, the native discourse, represented by its productive worke-rs, as well as its spatial organization and the objects on sale there. ln order to develop this approach, a theoretical analysis was made of the statutes that rule the local of the Feira Hippie, in addition to its relationship with the Ipanema neighborhood, with Rio de Janeiro City, and its function in a system of global tourism. This analysis was counterbalanced by field research which involved interviews, questionnaires, a photographic inventory and direct observations.